Survival after lumpectomy and mastectomy for early stage invasive breast cancer: the effect of age and hormone receptor status - Hwang, E. Shelley (2013)
BACKGROUND: Randomized clinical trials (RCT) have demonstrated equivalent survival for breast conserving therapy with radiation (BCT) and mastectomy for early stage breast cancer. We studied a large, population-based series of women who underwent BCT or M to observe whether outcomes of RCT were achieved in the general population, and whether survival differed by surgery type when stratified by age and hormone receptor (HR) status. METHODS: We obtained information regarding all women diagnosed in the state of California with stage I or II breast cancer between 1990 and 2004, treated with either BCT or mastectomy and followed for vital status through December 2009. We used Cox proportional hazards modeling to compare overall survival (OS) and disease-specific survival (DSS) between BCT and mastectomy groups. Analyses were stratified by age group (<50 years and ≥50 years) and tumor hormone receptor (HR) status. RESULTS: 112,154 women fulfilled eligibility criteria. Women undergoing BCT had improved OS and DSS when compared to women with mastectomy (adjusted HR for OS entire cohort 0.81, 95% CI 0.80 – 0.83). The DSS benefit with BCT compared to mastectomy was greater among women age≥50 with HR-positive disease (HR 0.86, 95% CI 0.82–0.91) than among women age<50 with HR-negative disease (HR 0.88, 95% CI 0.79–0.98); however, this trend was seen among all subgroups analyzed. CONCLUSION: Among patients with early stage breast cancer, BCT was associated with improved DSS. These data provide confidence that BCT remains an effective alternative to mastectomy for early stage disease regardless of age or HR status.